Analysis of double-diffusion convection on three-dimensional MHD stagnation point flow of a tangent hyperbolic Casson nanofluid. Issue 1 (31st December 2022) - Oyelakin, I. S.; Lalramneihmawii, P. C.; Mondal, S.; Sibanda, P.
ABSTRACT: In this paper, we present a numerical study of three-dimensional tangent hyperbolic Casson-nanofluid flow past a horizontally stretched surface with a magnetic field and double-diffusion convection. Double-diffusion convection in three-dimensional tangent hyperbolic Casson nanofluid flow together with slip coefficients, to the authors' observation, has not been studied. Hence, this study discusses the impact of double-diffusion convection on the magnetohydrodynamic stagnation point flow of a tangent hyperbolic Casson nanofluid. The nonlinear flow partial differential equations with the associated boundary conditions are reduced to a coupled system of nonlinear ordinary differential equations using appropriate similarity transformations. The ordinary differential equations are solved using the spectral local linearisation method. We study the significance of the magnetic field, Weissenberg, Prandtl, Soret and Dufour numbers on the fluid properties. The results indicate that increasing the Weissenberg numbers increases the relaxation time and leads to a resistance in the fluid flow in both the tangential and transverse directions. The temperature and concentration profiles are enhanced as a result of increasing the Weissenberg number.